Islamic Economics: A Survey Related to The Literature of Working Women - Nur Azizah, Siti (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
Various issues related to women are significant concerns across different layers of society. These issues are often constructed by the socio-cultural systems in which individuals reside, leading to various justifications being put forward. This phenomenon has inevitably sparked debates, including among Muslims. This study tries to build a concept related to women working through a literature Islamic economic approach. Classification of various concepts proposed by Al-Quran, Hadist, Islamic economists, Maqashid al-Syariah will also be discussed. This paper is a survey of the literature on Islamic economics which focuses on the Working Women and Islamic approaches through the Koran, hadith, opinions of scholars, maqashid sharia perspective, to produce the concept of working women. By this observation, we will be able to produce the concept of working women in Islam and to see the different points of view among the scholars in conceiving working women subject matter, as well as see the shades of thought in the object of study. The research findings indicate that Islam upholds the value of equality, with no prohibition against women working outside the home. However, Islamic law sets certain boundaries. Women who work are expected to prioritize the well-being of their families and communities while viewing their work as an act of worship